α-Glucosidase Inhibitory Activity of Resin From Sakhalin fir Tree ( Abies sachalinensis ) and its Bioactive Compounds ... - Nakagawa, Toshinori; Ashour, Ahmed; Yhiya Amen; Koba, Yurie; Ohnuki, Koichiro; Kuniyoshi Shimizu (Figshare, 2019)
This study investigated in vitro the α-glucosidase inhibitory activity of resin from the Sakhalin fir tree ( Abies sachalinensis ). The resin showed extremely high activity (IC 50 of 17.3 µg/mL). We isolated 8 compounds from the resin and identified them. All of the compounds isolated from A. sachalinensis resin are reported for the first time in the present study. In an α-glucosidase inhibitory assay, 6 compounds—(holophyllane C ( 1 ), (−) - (24 E )-23-oxo-3,4- seco -9β H -lanosta-4(28),6,8(14),24-tetraen-3,26-dioic acid ( 2 ), abiesonic acid ( 3 ), (−) - (24 E )-23-oxo-3,4- seco -9β H -lanosta-4(28),7,24-triene-3,26-dioic acid ( 4 ), 3,4- seco -4(28),6,8(14),22Z,24-mariesapentaen-26,23-olide-3-oic acid ( 5 ), and (−) - abiesonic acid 3-methyl ester ( 6 ))—showed high activity (their IC 50 values were 25.1, 20.9, 82.4, 20.5, 27.3, and 20.5 µg/mL, respectively). These compounds should contribute to the resin’s α-glucosidase inhibitory activity. From an industrial point of view, these findings provide new ...